Eligibility of E-Module Biology Material Cell-Assisted Flipping Book - Mellisa Mellisa; Delma Saputri; Indah Rahmadani (Jurnal BIOEDUIN : Program Studi Pendidikan Biologi, 2025)
This study aims to produce an e-module of biology teaching materials based on flipping books on cell material for grade XI high school. This study is a research and development (R&D) research with the ADDIE model (analysis, design, development, implementation, and evaluation), but it is limited to the development stage. This e-module is made using the flipping book application. The sampling technique in this study is purposive sampling. The sample used in this study was 45 high school students. The results of this study indicate that the quality of the validity of the e-module of teaching materials based on the results of the Validation of learning experts falls into the very valid category with an average of 99.06% (very valid), the results of the Validation of material experts get an average of 94.44% (very valid), the results of the Validation of media experts get an average of 92.98% (very valid), and the results of the Validation by three biology teachers get an average percentage of 95.55% (very valid). The trial results showed that students earned an average of 92.07% (very good); based on several categories, the developed e-module of learning is very valid and can be used as teaching materials to help students' learning process.